Centralization of Prehospital Triage Improves Triage of Pediatric Trauma Patients. Issue 1 (January 2021) - Gutierrez, Peter S.; Travers, Curtis; Geng, Zhi; Little, Wendalyn K.
Abstract : Introduction: This study describes the experience at a level 1 pediatric trauma center before and after the centralization of prehospital trauma triage, focusing on the rate of undertriage of trauma patients. Before centralization, emergency physicians were responsible for triaging these patients with mainly physiology-based criteria; after centralization, paramedics in a communication center performed this function using the same criteria. Methods: This retrospective study includes 10 years of pediatric trauma registry patients at our institution, 5 years before and after centralization of prehospital triage. Rates of undertriage were calculated by both the Cribari Method and by disposition from the emergency department. Logistic regression was used to assess the effect of centralization on the incidence of undertriage while adjusting for differences in case-mix. Results: Over the 10-year study period, 1862 trauma activations meeting inclusion and exclusion criteria were recorded in the trauma registry: 893 patients in the precentralization and 969 in the postcentralization groups. After centralization of the triage process, there were statistically significant decreases in the rates of undertriage from 8.7% to 4.2% (adjusted odds ratio, 0.49; 95% confidence interval, 0.33–0.73) when analyzed by the Cribari Method and from 37.7% to 27.7% when analyzed by disposition from the emergency department (adjusted odds ratio, 0.66; 95% confidence interval, 0.64–0.81). This represents a reduction in undertriage by 51.7% and 26.5%, respectively. Conclusions: Centralization of prehospital trauma triage at a level 1 pediatric trauma facility significantly reduced undertriage rates. Trauma centers should consider similar processes to improve prehospital triage.